Strategi Guru PAI dalam Meningkatkan Kualitas Sholat Berjamaah Siswi di SMA Nabil Husein Samarinda - Walid, M Nafiul; Sholihah, Aam Amaliatus; Lismina, Lismina (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Abstract This study discusses the strategies used by Islamic Religious Education teachers to improve the quality of congregational prayers of female students at SMA Nabil Husein Samarinda. Some of the problems faced by several female students at SMA Nabil Husein Samarinda are being undisciplined, not participating in wiridan, being unprepared, and being noisy during congregational prayers. All of these problems affect the quality of congregational prayers. This study aims to improve the quality of congregational prayers of female students at SMA Nabil Husein Samarinda. This study is descriptive qualitative, meaning it aims to provide a complete picture of the subject. The data sources in this study were the Principal, Islamic Religious Education Teacher, Deputy Curriculum, and six female students at SMA Nabil Husein Samarinda. The data analysis technique is qualitative data analysis which is carried out interactively and periodically until finished, when the data becomes saturated. The results of the study indicate that Islamic Religious Education teachers use four strategies to improve the quality of congregational prayers. These strategies include punishment, habituation, role models, and advice strategies. Five indicators are used as a reference in supporting this effort including solemnity in prayer, harmony of movements between congregations, accuracy of reading, physical and mental presence, and behavior and attitude after prayer. Based on the results of the study, this effort was able to improve the quality of congregational prayer of female students actively and consistently, discipline them to be present on time, and encourage positive changes in their attitudes and behavior. Keywords: Strategy, Islamic Religious Education Teachers, Quality, Congregational Prayer. Abstrak Penelitian ini membahas strategi yang digunakan guru PAI untuk peningkatan kualitas sholat berjamaah siswi di SMA Nabil Husein Samarinda. Beberapa masalah yang dihadapi beberapa siswi SMA Nabil Husein Samarinda adalah tidak disiplin, tidak ikut wiridan, tidak siap, dan ribut saat sholat berjamaah. Semua masalah ini memengaruhi kualitas sholat berjamaah. Studi ini bermaksud guna menumbuhkan kualitas sholat berjamaah siswi di SMA Nabil Husein Samarinda. Penelitian ini bersifat deskriptif kualitatif, artinya bertujuan untuk memberikan gambaran lengkap tentang subjeknya. Sumber data dalam penelitian ini adalah Kepala Sekolah, Guru PAI, Waka Kurikulum, dan enam siswi SMA Nabil Husein Samarinda. Teknis analisis data yaitu analisis data kualitatif yang dilaksanakan secara interaktif serta secara berkala hingga selesai, sesampainya data menjadi jenuh. Perolehan studi menunjukkan bahwasanya guru PAI menggunakan empat strategi untuk meningkatkan kualitas sholat berjamaah. Strategi ini termasuk hukuman, pembiasaan, keteladanan, serta strategi nasihat. Lima indikator digunakan sebagai acuan dalam mendukung upaya ini meliputi kekhusyukan dalam salat, keselarasan gerakan antar jamaah, ketepatan bacaan, kehadiran fisik dan mental, serta perilaku dan sikap setelah salat. Berdasarkan hasil penelitian upaya ini mampu meningkatkan kualitas salat berjamaah siswi secara aktif dan konsisten, mendisiplinkan mereka untuk hadir tepat waktu, serta mendorong perubahan positif dalam sikap dan perilaku mereka. Kata Kunci: Strategi, Guru PAI , Kualitas, Sholat Berjamaah.